Endogenous development: can it be duplicated? - Koehnen T.L.; Alves A.P.V. (Strengthening endogenous development patterns in European agriculture, 1993)
This paper traces and describes how a group of young farmers was mobilised to improve economic and social conditions. This took the form of a local endogenous initiative. This study was carried out using a case-study approach, and included group and individual interviews, questionnaires, secondary data and data from key informants.
Seminar on 'Strengthening Endogenous Development Patterns in European Agriculture', 1992/10/20-22, Chania (Greece)